Meningococcal disease outbreak related to the World Scout Jamboree in Japan, 2015 - Kanai, Mizue; Kamiya, Hajime; Smith-Palmer, Alison; Takahashi, Hideyuki; Hachisu, Yushi; Fukusumi, Munehisa; Saitoh, Takehito; Ohnishi, Makoto; Sunagawa, Tomimasa; Matsui, Tamano; Oishi, Kazunori (Western Pacific Surveillance and Response, 2017)
Problem: Six invasive meningococcal disease cases occurred among Scottish and Swedish nationals associated with the World Scout Jamboree (WSJ), an international mass gathering, held in Japan. The index case developed symptoms while returning home. The strains from all six cases were identical and seldom seen in Japan. Context: Over 33 000 participants from 155 countries attended WSJ. At the Jamboree site, participants of the North of Scotland’s and Sweden’s units camped within the same subcamp and kept the same schedule of events. No information was available about the Swedish and Scottish cases’ close personal contact history. Action: Health Protection Scotland investigated Scottish cases, conducted active case finding, provided chemoprophylaxis, vaccinated close contacts and advised Scottish WSJ participants and contacts to seek medical care if they developed symptoms. The Public Health Agency of Sweden recommended chemoprophylaxis to all participants in Sweden. In Japan, the Ministry of Health, Labour and Welfare (MHLW) requested the Scout Association of Japan advise all participants to seek medical attention if they developed symptoms. MHLW shared information about the event with local authorities, medical associations, and the Ministry of Education, Culture, Sports, Science and Technology. Outcome: No additional case related to WSJ has been reported. This outbreak highlighted the risk for international spread of invasive meningococcal disease at international mass gatherings. Discussion: Assessing risk, educating participants, enhancing surveillance and sharing timely information among related countries are significant for prevention and response against invasive meningococcal disease outbreaks at mass gatherings.